Verification of stereotactic cranial radiotherapy treatments with MR-based gel dosimeters: practical aspects. (August 2019) - Costa, Filipa; Kousi, Evanthia; Gasnier, Anne; Wells, Emma; Lamb, Caroline; Schmidt, Maria A; Moore, Rollo
Abstract: Image Guided Radiotherapy (IGRT) systems allow delivering high doses of radiation to a tumour with great precision and accuracy. In this work, we use patient-specific head MR-based gel dosimeters as an end-to-end test to commission IGRT delivery systems, for stereotactic cranial radiotherapy, and investigate possible sources of errors associated with practical aspects of the measurements. A CT scan of a patient is used to 3D print the shape of the cranial bones to create head phantoms with MR-based gel inside. Each phantom was used as a patient, following the radiotherapy workflow which includes: taking a CT scan of the phantom, calculating the dose distribution using a treatment planning system (TPS) and delivering the radiation calculated by the TPS (to target three different lesions: Big, Medium and Small). Each phantom was then scanned on an MR scanner to obtain a T2 map (linear with dose), which was then rigidly registered with the CT scan of the phantom based on the phantom structures. Good agreement was obtained between the normalized R2 (=1/T2) values and TPS simulations. The relationship between R2 values and dose was investigated based on 3D regions including each lesion. Good linearity was found, but different R2-dose values relationship was obtained depending on the selected regions. The impact of applying a registration based on each lesion (and not the phantom structures) was also tested. Results show that the registration has an impact on the relationship between R2 values and dose, and although absolute dose measurements are still not possible with these MR-based gel dosimeters, they provide very detailed geometrical 3D information to validate IGRT radiotherapy treatments with high level of accuracy.